Pengaruh kualitas pelayanan Ijin Mendirikan Bangunan (IMB) terhadap kepuasan masyarakat - Henny Wuryanti K; Nurita Andriani; Mohammad Arief (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2018)
The study aims to determine the effect of the quality of licensing services for Building Construction Permits (IMB) including physical evidence, reliability, responsiveness, assurance, empathy for community satisfaction in the services of the Public Works Office of Cipta Karya and Spatial Planning in Surabaya. The sampling technique uses purposive sampling with a sample size of 187, using data analysis is PLS (Partial Least Square). The results showed that physical evidence, reliability, responsiveness, assurance, and empathy had a significant positive effect on community satisfaction of users of IMB permit services in Surabaya Public Works and Spatial Planning Office.